Editorial - The Editors (Laureate Education Inc, 2012)
Academic research represents a milestone in the practice of quality higher education.  Academics that consistently conduct and publish research in specialized disciplines develop leadership in their particular areas and nurture with new knowledge disciplines and professions. Certainly they strengthen the critical atmosphere in which students study and contribute to the reputation of the institutions in which they teach, and by segue attracting highly qualified students and new promising faculty into their programs.  Ground-breaking knowledge is often developed at graduate degree programs, that is, after all, how the practice of academia grows its expertise. Research is a tool for both academia and industry, providing both the framework and opportunity to explore and discover new knowledge and ideas, and strengthening higher education by encouraging the continued debate and challenge of peer-to-peer collaboration. The special issue celebrates quality of research as a basis of higher education.   Since Higher Learning Research Communications focuses on policy and practice in higher education, we have dedicated this special issue to the practice of paramount research in specialized fields of study.  This issue is published as a demonstration of how academicians and practitioners can work as peers to provide a global scope. As a festschrift of Glion Institute of Higher Education's 50th anniversary, we dedicate this special issue to "Tourism, Hospitality and Leisure in a Globalized World"   Overlooking the magnificent Lake Geneva in Switzerland, Glion is one of the world's leading schools of international hospitality education. Ranked among the top hospitality management schools in the world for an international career, and celebrated by the global hospitality industry, Glion has been at the top of higher education providers in this realm by recognizing early on that neither job experience nor books alone can grant a student a high-quality education. As this fast-paced, industrialized world increasingly requires schools to train their students with not only theoretical knowledge, but also practical, measurable, and technical skills, Glion has recognized this trend and integrated key components in its curriculum to confront the challenges and seize that opportunities that the school and its students will face.   Being a hospitality higher education institution, Glion has a strong business curriculum delivered by expert faculty members and is committed to continuously adapting its programs to meet the needs of the modern capitalist world. As with many other fields, market trends, governmental policies, eco-consciousness and innovative business practices have impacted the tourism industry. Guest Editors Ruth Rios-Morales and Ian Jenkins, both from Glion, were asked to put together a Journal Issue that represents the state-of-the-art research in the discipline.  We hope you will enjoy this special edition - and whether you are involved in the hospitality and tourism industry or not, will recognize the quality of research that nurtures in a relevant manner higher education programmers in this field. The Editors